Learning From Others and Spontaneous Exploration: A Cross‐Cultural Investigation. Issue 3 (May 2016) - Shneidman, Laura; Gweon, Hyowon; Schulz, Laura E.; Woodward, Amanda L.
Abstract : How does early social experience affect children's inferences and exploration? Following prior work on children's reasoning in pedagogical contexts, this study examined U.S. children with less experience in formal schooling and Yucatec Mayan children whose early social input is predominantly observational. In Experiment 1, U.S. 2‐year‐olds ( n = 77) showed more restricted exploration of a toy following a pedagogical demonstration than an interrupted, accidental, or no demonstration (baseline). In Experiment 2, Yucatec Mayan and U.S. 2‐year‐olds ( n = 66) showed more restricted exploration following a pedagogical than an observational demonstration, while only Mayan children showed more restriction with age. These results suggest that although schooling is not a necessary precursor for sensitivity to pedagogy, early social experience may influence children's inferences and exploration in pedagogical contexts.